Penerapan Rasa Bela Negara Pada Generasi Muda Di Era Globalisasi - Rio Saputro; Fatma Ulfatun Najicha (FKIP, Universitas Palangka Raya, 2022)
Talking about defending the country will certainly cross our minds, namely efforts to defend a nation and state. The meaning of defending the country itself is defined as the attitude or behavior of citizens who are imbued with a sense of nationalism based on Pancasila and the 1945 Constitution in living the life of the nation and state. The purpose of defending the state is to maintain the survival of the nation and state, preserve culture, and apply the values ​​of Pancasila and the 1945 Constitution. This era of globalization has caused many serious problems with patriotism and nationalism of our nation, technology in all fields, especially Information technology is a necessity that we cannot avoid where people can easily access good and bad information through internet networks around the world. This turns out to have an impact on life in our society today. As a result of unstoppable information, the impacts include the lower and the fading of the nation's cultural values, social solidarity, and the emergence of radicalism that can threaten the country